Best of Discovery Channel. Volume 3, Dragons a fantasy made real - Hardy, Justin; Stewart, Patrick, 1940-; Animal Planet (Television network); Discovery Channel (Firm) ([S.l.] : Discovery Channel, 2006)
Using computer-generated imagery, shows how dragons could have evolved into a number of different species through the ages and how each species might have adapted to its environment.
Keywords: Dragons